Analisis Sentimen Terhadap Calon Wakil Presiden Gibran Rakabuming Raka Menggunakan Algoritma Naive Bayes - Nursyarif, Muhammad Khumaidi; Tirta, Muhamad Wahyu; Hidayat, Muhammad Rahman; Rudiman, Rudiman (KOMPUTEK, 2024)
The turnover of the president and vice president in Indonesia occurs every 5 years. In the year 2024, there will be an election, and one of the vice presidential candidates, listed as candidate number 2, is Gibran Rakabuming Raka, who is the son of Mr. Jokowi, currently serving as the 7th President. Many opinions have been expressed by the public regarding Mas Gibran, especially considering his age of 36 years, which is perceived as relatively young to lead the nation of Indonesia. Therefore, we intend to conduct research with the aim of identifying practical implications related to public perceptions of the potential vice presidential candidate. Data from comments on the YouTube video titled "[FULL] Gibran in Between Ganjar and Prabowo, Which One to Choose? | ROSI" underwent a classification process using the Naive Bayes algorithm for sentiment analysis. The accuracy obtained is 92.5%, with an f1 Score of 92.4%, Precision of 93.5%, and Recall of 92.5%.